Attitude of School Students Towards the Use of Information and Communication Technology (ICT) in Rural and Urban Areas of West Bengal: A Study (International Journal of Food and Nutritional Sciences, 2023)
Information and Communication Technology (ICT) refers to a combination of technological tools and resources used for communication, information processing, storage, and dissemination. In the field of education, ICT has become an essential medium for improving teaching-learning practices and increasing students’ interest in academic activities. The present study examines the attitude of secondary school students towards the use of ICT in both rural and urban areas of West Bengal. It also explores the use of ICT for educational and non-educational purposes and identifies the major barriers faced by students in accessing ICT facilities. The research was conducted in secondary schools equipped with ICT facilities in Kolkata and South 24 Parganas districts. The findings indicate that ICT creates significant opportunities for students when the available resources are effectively utilized.